RETROSPECTIVE DOSE RECONSTRUCTION WITH MOBILE PHONES AND CHIP CARDS. Issue 2 (11th November 2019) - Ekendahl, Daniela; Čemusová, Zina; Judas, Libor
Abstract: Mobile phones and common chip cards are very widespread items that almost everyone owns. They contain some radiation-sensitive materials that can be used for dosimetry based on stimulated luminescence. We investigated and compared reproducibility, dose response and fading of luminescence signal for the particular materials. Subsequently, we performed an experiment of a dose reconstruction using mobile phones and chip cards, which were fixed to a slab phantom and irradiated by a 137 Cs radiation source in our laboratory. Doses obtained were compared with reference values. The materials investigated can be used for dosimetry in cases of serious radiation accidents or malevolent acts with radioactive materials, when it is extremely important to identify as quickly as possible individuals who received high-radiation doses.